Focusing on structural changes and future risks of ecosystems: An opportunity-cost based ecosystem service account for riparian ecosystems and its case study - Shenbei Zhou; Yuanyuan Huang; Hai He; Zixia Zhang (Ecological Indicators, 2024)
The riparian is a buffer zone between the river and human society, and improper land development will increase the ecological vulnerability of the river basin. Different evaluation methods for the ecological impact of development behavior will produce different value perception results, which in turn will affect the judgment and choice of decision-makers and the public. Based on the construction of an opportunity-cost-based monetary valuation method in the SEEA-EA (System of Environmental Economic Accounting-Ecosystem Accounting), this study took the riparian under the influence of the Xiaolangdi Project of the Yellow River from 1990 to 2020 as the research object, and evaluated the impact of land development decisions on ecosystem services under the superimposed influence of major projects, policies and socio-economic changes. The results show that: (1) The inclusion of opportunity costs can reduce the distortion of ecological value caused by economic factors and supply–demand state. In the case study, the opportunity cost of each 5-year accounting period in 30 years reduced the total accounting value respectively by 196.76, 25.88, 80.57, 84.33, 27.96, and 577.48 million yuan. (2) Opportunity cost can effectively reflect the ecological profit and loss caused by land transformation between different ecosystem types caused by decision-making in different periods. From 2015 to 2020, the opportunity cost of ecosystems was high when the total ecological land in the riparian increased, which reflected the drastic changes in land use during the decision-making period. (3) Opportunity costs are included in the monetary account as part of the “stock reduction”, which directly reflects the risk of ecological land reduction and structural change caused by development behavior. This mixed account of physical and monetary stocks can reflect both physical changes in ecosystem services and ecological risks, thereby improving stakeholders’ scientific understanding of the fluctuations in the value of ecosystem services caused by riparian land use.